Contentious Terrains : Boglands in the Irish Postcolonial Gothic - Gladwin, Derek (Book collections on Project MUSE., 2016)
This book provides a political and geographical history of how boglands (or peat bogs) are represented in modern and contemporary Irish literature and culture from the 1880s to the present. Bogs are more than ubiquitous landforms in Ireland. They function as a kind of narrative that reveals some of the potentially unanswered questions in an Irish literary geo-history, particularly leading up to and during the Land Wars of the 1880s, Irish War of Independence (1919-1921), the "Troubles" (1960s and 1970s), Celtic Tiger (1990s and 2000s), and into the current environmental crisis. The overlap of the postcolonial and the Gothic -- across ecological, spatial, social, and gender approaches -- serves as an effective way to address some historical layers and apparent contradictions in literary representations of bogs in Ireland. Drawing on a range of Irish writers, including Bram Stoker, Frank O'Connor, Sean O'Faolain, Daniel Corkery, Seamus Heaney, Marina Carr, Deirdre Kinahan, Patrick McCabe, and Tim Robinson, Contentious Terrains, ultimately argues that the destabilizing and haunting capacities of the bog provide a space to explore historically fraught colonial tensions and social struggles through the Gothic form. It employs a cross-disciplinary scope, examining an assortment of Irish writers in the literary genres of fiction, poetry, drama, and non-fiction, thus testifying to the pervasiveness and range of the bog's allure in Irish culture.